Morphometric Characteristics, Polyphenols and Ascorbic Acid Variation in Brassica oleracea L. Novel Foods: Sprouts, Microgreens and Baby Leaves - Maria Concetta Di Bella; Agnieszka Niklas; Stefania Toscano; Valentina Picchi; Daniela Romano; Roberto Lo Scalzo; Ferdinando Branca (Agronomy, 2020)
In the present study, we investigated the content and profile of polyphenols (PPH), ascorbic acid (AA), the Folin–Ciocalteu index (FCI), and antioxidant activity (1,1-diphenyl-2-picrylhydrazyl (DPPH) and peroxyl radical (ROO)) variation during three different plant growth stages (sprouts, microgreens and baby leaves) of two broccoli types, the traditional Sicilian sprouting broccoli landrace (‘Broccolo Nero’) and the broccoli standard (‘Cavolo broccolo Ramoso Calabrese’), and the standard commercial cultivar of kale (‘Cavolo Lacinato Nero di Toscana’). All biomasses collected were freeze-dried for PPH, AA, FCI, DPPH and ROO analysis. The highest polyphenol content was observed for ‘Broccolo Nero’ (BN) and ‘Cavolo Broccolo Ramoso Calabrese’ (CR), and generally sprouts showed significantly higher values compared to the microgreens and the baby leaves. The AA, FCI, DDPH and ROO significantly vary with regards to the cultivar and the plant growth stage, showing interaction between the two experimental factors analyzed. The interaction detected showed higher values for the antioxidant traits of the proposed novel food, especially for the two broccoli cultivars in the sprout growth stage in comparison to the microgreens and baby leaves. Our results suggest that the antioxidant activity is partially dependent on kaempferol and apigenin. The PPH compounds showed the highest values of kaempferol and apigenin for ‘Broccolo nero’, whereas for the other two cultivars studied, only kaempferol was the main compound represented. The data acquired are of interest for increasing the healthy traits of the novel food proposed showing the contribution offered by the neglected LRs until now underutilized and at risk of extinction. The germplasm conserved in several world genebanks could support and diversify the organic vegetable items, providing us with added-value products for organic food supply chains.